Science Literacy Profile of Junior High School Students on Global Warming Material - Setyaningsih, Setyaningsih; Roshayanti, Fenny; Nizaruddin , Nizaruddin; Khoiri, Nur (Universitas Negeri Semarang, 2024)
Understanding science literacy is essential to facilitating effective learning and effectively addressing environmental concerns, as global warming is a complex subject. The purpose of this study is to map the science literacy profile of junior high school students in grade 7 regarding global warming content. Using multiple-choice exams and interviews, a descriptive quantitative method is employed to gather data on science context, science content, scientific competence, and science attitudes. 64 grade 7 students from SMP Negeri 1 Sambong in the Blora district participated in this study. According to the findings, 50% of students' science literacy in the area of global warming fell into the